A tale of two power transitions: Capabilities, satisfaction, and the will to power in the relations between the United Kingdom, the United States, and Imperial Germany. (September 2017) - Rauch, Carsten
Given the current redistributions in the global balance of power, power transition theory (PTT) has once again become an important intellectual factor. Many observers employing PTT are anxious about China's ascendance and expect serious conflicts between Washington and Beijing in the coming years. Such skepticism, however, is problematic for three reasons. First, it is false theoretically; PTT does not claim that all rising powers will resort to war or that all power transitions will result in war. Second, it is false empirically; not all power transitions in history have resulted in Great Power wars. Third, it leads to flawed policy advice; if rising powers are not always dissatisfied and do not always challenge the status quo, then policies meant to oppose them might breed dangerous dissatisfaction in the first place. This article amends PTT by adding a variable, the "will to power" (WTP), that captures the willingness of rising powers to commit themselves to changing the status quo. Furthermore, it scrutinizes two historical power transition constellations (United Kingdom–United States and United Kingdom–Imperial Germany). In both cases the new variable is consistent with the outcome and particularly in the United Kingdom–United States case the WTP variable broadens our understanding by making it possible to see this relationship as "missed" or "eschewed" instead of as a peaceful power transition. Doing so extends the power transition dichotomy to a much more complex and realistic typology of power transition constellations.